2013
DOI: 10.1021/bi400066a
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Phosphoryl Transfer Catalyzed by cAMP-Dependent Protein Kinase: An X-ray Crystallographic Study of Complexes with Various Metals and Peptide Substrate SP20

Abstract: X-ray structures of several ternary substrate and product complexes of the catalytic subunit of cAMP-dependent protein kinase (PKAc) have been determined with different bound metal ions. In the PKAc complexes, Mg2+, Ca2+, Sr2+, and Ba2+ metal ions could bind to the active site and facilitate the phosphoryl transfer reaction. ATP and a substrate peptide (SP20) were modified, and the reaction products ADP and the phosphorylated peptide were found trapped in the enzyme active site. Finally, we determined the stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
79
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(91 citation statements)
references
References 36 publications
(74 reference statements)
12
79
0
Order By: Relevance
“…In addition, we recently obtained an x-ray structure of the PKAc-Ca 2 ADP-pSP20 complex, in which the ADP and phosphorylated SP20 products were captured in the active site (8). Comparison of our current pseudo-Michaelis complex with the transition state mimic and the product allows us to visualize structural changes that may accompany the catalysis and to identify mechanistically important structural information.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, we recently obtained an x-ray structure of the PKAc-Ca 2 ADP-pSP20 complex, in which the ADP and phosphorylated SP20 products were captured in the active site (8). Comparison of our current pseudo-Michaelis complex with the transition state mimic and the product allows us to visualize structural changes that may accompany the catalysis and to identify mechanistically important structural information.…”
Section: Resultsmentioning
confidence: 99%
“…The structure is consistent with the S N 2 mechanism and demonstrates a short interaction between Asp-166 and the side chain of Ser-21 SP20 . Finally, PKAc product complexes have been trapped in crystals when ATP and SP20 were utilized (8). These structures, and enzyme kinetics measurements, demonstrated that, in addition to Mg 2ϩ , all other divalent alkaline earth metals, including Ca 2ϩ , Sr 2ϩ , and Ba 2ϩ , support the phosphoryl transfer to SP20 (14).…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…Interestingly, the Mg 2+ to Ca 2+ substitution effects are typically also similarly inhibitory 76 for two-metal ion catalysis as well as for the one-metal ion catalysis in dUTPase [21][22] and in several ATPases [77][78][79][80][81] and kinases 78,[82][83] with some notable exceptions. [84][85] This key metal ion often coordinates the cleaved phosphate. This helps the catalysis by lowering the pK a of the phosphate group.…”
mentioning
confidence: 99%